Avaliação dos efeitos morfofisiológicos e comportamentais em camundongos jovens submetidos ao estresse por separação maternal em conjunto com administração de L-Dopa - Ana Luiza de Araujo Lima Reis (2021)
Early life stress can lead to behavioral changes commonly associated with many of the neuropsychiatric disorders, including anxiety and depression. Several of these disorders appear during adolescence, when brain remodeling takes place. This is one of the reasons why the practice of child/adolescent psychiatry and preventive approaches is still a challenge. Therefore, we investigated the effects of maternal separation (MS) stress on the behavior of prepubertal mice. One of the challenges in psychiatry studies is the sexual bias in the prevalence of some mental disorders. To address this issue, we used C57 / BL6 male and female mice. At 4 weeks of age, we analyzed the behavior of the animals through locomotor activity box tests, open field test, light/dark box, elevated plus maze, novelty suppressed feeding test and forced swimming test. We have seen that postnatal stress led to an increase in exploratory and locomotor behavior in females and an increase in anxious-like and depressive-like behavior in males. In addition to the fact that several dopaminergic genes are associated with neuropsychiatric disorders and the dopaminergic system is the target of many pharmacological treatments, it is known that chronic stress generates imbalances in dopaminergic signaling. We then investigated whether increased dopaminergic tone through L-Dopa administration, in conjunction with MS stress, amplifies or reduces behavioral consequences in prepubertal mice. We divided the mice into four experimental groups: treated with saline solution (SAL); Group treated with L-Dopa / Benserazide (DOPA); MS treated daily with Saline (MS+SAL); and group treated with L-Dopa / Benserazide during MS (MS+DOPA). We saw that L-Dopa administration provided less aversion to more aversive environments in females and an increase in fearful behavior in males. We also saw that increased dopaminergic tone during postnatal stress was able to alter the behavioral effects of stress and our results suggest a sexual dimorphism in response to L-Dopa treatment during the maternal separation protocol.